Modeling and Simulation of a Continuous Biomass Hydrothermal Carbonization Process - Cubillos-Montecino, F; Diaz-Robles, L; Campos-Bravo, V; Pino-Cortes, E (Taylor and Francis Ltd., 2020)
This work evaluates a continuous biomass hydrothermal carbonization process through modeling and steady state simulation using the UniSim Design process simulator. The reactive process was divided into four stages: biomass hydrolysis, intermediate compounds degradation, aromatics formation, and polymerization process, which make it possible to obtain the solid product or hydrochar. Pure biomass types and their mixtures were compared, considering hydrochar and carbon yields, H/C, and O/C ratios, and their deviation from the batch process. The results of hydrochar yield indicated that biomass with high cellulose content can perform satisfactorily in the proposed model. In addition, the possibility of carrying out the process in reactive stages together with the recirculation of liquid product, allowed a greater yield with respect to the batch process. It is concluded that the proposed model improves the characteristics of the obtained hydrochar compared to its crude biomass, achieving lower proportions of hydrogen and oxygen in the solid product. © 2019, © 2019 Taylor & Francis Group, LLC.